27. DEVELOPMENT AND VALIDATION OF HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE QUANTIFICATION OF AFLATOXIN B1 IN HERBAL DRUGS AND CEREALS (Vietnam Journal of Community Medicine, 2025)
Objectives: A high-performance liquid chromatography method was developed and validated for the quantification of Aflatoxin B1 in Herbs and cereals.Method: The proposed method was validated according to ICH guidelines for specificity, repeatability, linearity, accuracy, and precision.Results: The method was achieved including Waters C18 column (50 mm × 2.1 mm; 1.7 µm), the mobile phase contained aqueous 0.1% phosphoric acid:acetonitrile 0.2% (33:67) in isocratic with flow rate of 0.2 ml/min, injection volume of 20 μl, and detector PDA-UV at 354 nm. The developed method showed the present of Aflatoxin B1 in 2 Herbs and cereals samples, account for about 2% of samples analyzed.Conclusion: The study was successfully developed and validated high-performance liquid chromatography method for quantification of Aflatoxin B1 in Herbs and cereals. This is the background for further studies.
Keywords: Herbal drugs, cereals; Aflatoxin B1; high-performance liquid chromatography.